2018
DOI: 10.1016/j.jaci.2017.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Excessive gestational weight gain in first trimester is a risk factor for exacerbation of asthma during pregnancy: A prospective study of 1283 pregnancies

Abstract: Excessive GWG in the first trimester is a risk factor for asthma exacerbation during pregnancy and the risk increases in a dose-dependent manner with increasing GWG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 25 publications
1
32
0
1
Order By: Relevance
“…Appropriate pregravid weight and gestational weight gain (GWG) are essential to obtaining a favorable delivery outcome and promoting mother and infant health. Previous studies have reported that inadequate gestational weight gain is associated with low birth weight and preterm births [1,2], while excessive gestational weight gain increases the risks for not only gestational diabetes mellitus, preeclampsia, macrosomia, postpartum weight retention, and offspring obesity [35], but also for non-pregnancy-related diseases, such as asthma, during pregnancy [6]. Since twin birth rates have been increasing worldwide in recent decades due to improvements in assisted reproductive technology, the greater number of women conceiving at older ages, and the differences in the special physiological characteristics with singleton pregnancy, it is necessary to study the correlations of GWG with the pregnancy complications and pregnancy outcome of twin pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate pregravid weight and gestational weight gain (GWG) are essential to obtaining a favorable delivery outcome and promoting mother and infant health. Previous studies have reported that inadequate gestational weight gain is associated with low birth weight and preterm births [1,2], while excessive gestational weight gain increases the risks for not only gestational diabetes mellitus, preeclampsia, macrosomia, postpartum weight retention, and offspring obesity [35], but also for non-pregnancy-related diseases, such as asthma, during pregnancy [6]. Since twin birth rates have been increasing worldwide in recent decades due to improvements in assisted reproductive technology, the greater number of women conceiving at older ages, and the differences in the special physiological characteristics with singleton pregnancy, it is necessary to study the correlations of GWG with the pregnancy complications and pregnancy outcome of twin pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Women with asthma were included in the MAP cohort provided they fulfilled the following criteria: 1) they possessed a diagnosis of asthma as defined according to the GINA-guidelines [10]; 2) they were receiving current prescribed treatment with at least a rescue bronchodilator; and 3) they had their first visit to the respiratory outpatient clinic within the first 18 weeks of pregnancy. A more detailed description of the MAP cohort has been published previously [11][12][13]. Only women from the MAP cohort with a live birth were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The Management of Asthma during Pregnancy (MAP) programme was initiated in 2007, and participants for this study were consecutively recruited through the Department of Obstetrics and Gynaecology, Hvidovre Hospital, Denmark. The MAP study has been described in detail previously …”
Section: Methodsmentioning
confidence: 99%
“…The MAP study has been described in detail previously. [11][12][13][14] Inclusion criteria were as follows: case history, addressing the number and severity of any previous asthma exacerbations, tobacco exposure, and prescribed asthma medication was obtained. The importance of adherence with controller medication was addressed, and inhaler device technique checked.…”
Section: Methodsmentioning
confidence: 99%